‘Evil never dies, right?’ Monstrous mediation in the A Nightmare on Elm Street Film Series - Morten Feldtfos Thomsen (Journal of Aesthetics & Culture)
This article investigates images of mediation in the A Nightmare on Elm Street film series, focusing primarily on its main antagonist, Freddy Krueger, and his monstrous uses of media. Employing Eugene Thacker’s concept of “dark media”, as well as Gary Heba’s reading of the Nightmare series as centering on the confrontation between youth and the dominant societal order of patriarchal capitalism, this article argues that the series articulates a highly ambivalent image of mediation, which is intimately connected to its thematic interest in issues concerning power and emancipation. Moreover, it argues that this ambivalent image of mediation ultimately constitutes a self-reflexive engagement with the potential cultural work of the Nightmare series itself.